Scale dependence of environmental controls on the functional diversity of coral reef fish communities. Issue 10 (October 2017) - Yeager, Lauren A.; Deith, Mairin C. M.; McPherson, Jana M.; Williams, Ivor D.; Baum, Julia K.
Abstract: Aim: The functional composition of local assemblages is hypothesized to be controlled by hierarchical environmental filters, whereby the importance of different abiotic and biotic factors varies across both spatial scales and the different dimensions of functional diversity. We examine scale dependence in functional diversity–environment relationships with the ultimate aim of advancing models that predict the response of functional diversity to global change. Location: Coral reefs surrounding 23 minimally disturbed central‐western Pacific islands. Time period: 2010–2015. Major taxa studied: Coral reef fishes. Methods: We surveyed 1, 423 reef sites using a standardized monitoring protocol and classified the 547 taxa encountered based on traits related to resource use, body size and behaviour. For each fish community, we calculated species richness and three metrics of functional diversity: functional richness, functional redundancy and functional evenness. We then built nested models at three spatial scales to evaluate the predictive power of environmental conditions over each component of functional diversity. Results: Climatic variables (e.g., primary productivity) and geomorphic context (e.g., bathymetric slope) were more important in predicting functional diversity at coarse spatial scales. In contrast, local measures of habitat quality, including benthic complexity, depth and hard coral cover, were generally most important at finer scales. All diversity metrics were better predicted at coarser scales, but which predictors were important varied among metrics. Main conclusions: The observed scale dependence in environmental predictors of functional diversity generally matches models of hierarchical filters on functional community assembly. Contrary to expectation, however, functional evenness and functional redundancy, which incorporate information on biomass distributions, were not better predicted at finer spatial scales. Instead, broad‐scale variation in environmental variables was most important in predicting all components of functional diversity. Furthermore, the distinct responses of each functional diversity metric to environmental variation indicate that each measures a unique dimension of reef‐fish diversity, and environmental change may affect each differently.